Comparison of Two- and Three-dimensional Ultrasonography in the Evaluation of Lesion Level in Fetuses with Spina Bifida - Requeijo, Márcio José Rosa; Bunduki, Victor; Francisco, Rossana Pulcineli Vieira; Lopes, Marco Antonio Borges; Ruano, Rodrigo; Zugaib, Marcelo (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2016)
Purpose To evaluate the precision of both two- and three-dimensional ultrasonography in determining vertebral lesion level (the first open vertebra) in patients with spina bifida.Methods This was a prospective longitudinal study comprising of fetuses with open spina bifida who were treated in the fetal medicine division of the department of obstetrics of Hospital das Clínicas of the Universidade de São Paulo between 2004 and 2013. Vertebral lesion level was established by using both two- and three-dimensional ultrasonography in 50 fetuses (two examiners in each method). The lesion level in the neonatal period was established by radiological assessment of the spine. All pregnancies were followed in our hospital prenatally, and delivery was scheduled to allow immediate postnatal surgical correction.Results Two-dimensional sonography precisely estimated the spina bifida level in 53% of the cases. The estimate error was within one vertebra in 80% of the cases, in up to two vertebrae in 89%, and in up to three vertebrae in 100%, showing a good interobserver agreement. Three-dimensional ultrasonography precisely estimated the lesion level in 50% of the cases. The estimate error was within one vertebra in 82% of the cases, in up to two vertebrae in 90%, and in up to three vertebrae in 100%, also showing good interobserver agreement. Whenever an estimate error was observed, both two- and three-dimensional ultrasonography scans tended to underestimate the true lesion level (55.3% and 62% of the cases, respectively).Conclusions No relevant difference in diagnostic performance was observed between the two- and three-dimensional ultrasonography. The use of three-dimensional ultrasonography showed no additional benefit in diagnosing the lesion level in the fetuses with spina bifida. Errors in both methods showed a tendency to underestimate lesion level.
Keywords: fetus; two-dimensional ultrasonography; three-dimensional ultrasonography; spina bifida